Comparative analysis of Unity and Unreal Engine efficiency in creating virtual exhibitions of 3D scanned models - Ciekanowska, Agata; Kiszczak - Gliński, Adam; Dziedzic, Krzysztof (Journal of Computer Sciences Institute, 2021)
The main purpose of this work was to compare two game engines (Unreal Engine and Unity) in creating virtual exhibitions. The article is a scientific description of a test of their efficiency. For the needs of the research two identical test applications built on the basis of the same assets were created. Those applications enabled researchers to examine and compare the efficiency of engines in question, as well as familiarizing themselves with the workflow on each platform. The comparative analysis of gathered data let more effective solution to emerge, which happens to be Unity engine.